2016
DOI: 10.1111/jvim.13981
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Magnetic Resonance Imaging for Evaluation of Disc‐Associated Cervical Spondylomyelopathy in Doberman Pinschers

Abstract: BackgroundThe dynamic component of disc‐associated cervical spondylomyelopathy (DA‐CSM) currently is evaluated using traction magnetic resonance imaging (MRI), which does not assess changes in flexion and extension of the cervical vertebral column. In humans with cervical spondylotic myelopathy, kinematic MRI is used to identify dynamic compressions.Hypothesis/ObjectivesTo evaluate the feasibility and utility of kMRI in Doberman Pinschers with DA‐CSM using a novel positioning device. We hypothesized that kMRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…This disorder results in secondary soft tissue changes, including protrusion of the intervertebral disc causing compression of the spinal cord. Caudal cervical discs, particularly C5‐6 and C6‐7, are the most commonly affected . Underlying vertebral canal stenosis lowers the threshold for the development of cervical hyperaesthesia and/or neurologic dysfunction secondary to spinal cord compression; however, intervertebral disc protrusion can be evident on advanced imaging without associated clinical signs …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This disorder results in secondary soft tissue changes, including protrusion of the intervertebral disc causing compression of the spinal cord. Caudal cervical discs, particularly C5‐6 and C6‐7, are the most commonly affected . Underlying vertebral canal stenosis lowers the threshold for the development of cervical hyperaesthesia and/or neurologic dysfunction secondary to spinal cord compression; however, intervertebral disc protrusion can be evident on advanced imaging without associated clinical signs …”
mentioning
confidence: 99%
“…Static and dynamic forces contribute to the pathophysiology of both DACSM and OACSM . Dynamic lesions have been diagnosed traditionally by traction myelography and more recently with kinematic advanced imaging …”
mentioning
confidence: 99%
“…Although in DA-CSM, concussive force and length of the compression do not commonly play a role, other equally complex forces may help explain the discrepancies found when dealing with DA-CSM [15]. The presence of dynamic lesions, for instance, may lead to divergences between spinal cord compression in neutral position and maximum spinal cord compression, since dynamic MRI has shown that extension and exion of the cervical vertebral column can affect the degree of spinal cord compression [20]. Total number of dogs investigated, variations in the neurologic grading system used, and different observer and measuring methods in each study may also help explain differences between studies.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical point of view, flexion and extension of the cervical vertebral column are two dynamic factors that might contribute to progression of disease of canine cervical spondylomyelopathy. 28 Extension creates a decrease in the diameter of the vertebral canal 29 and intervertebral foramina, which has been shown to worsen both spinal cord and nerve root compression. 28 In the light of these findings, it might be suggested that the increase in extension motion created by facetectomy leads to an increased instability if the method is used to treat dynamic lesions.…”
Section: Discussionmentioning
confidence: 99%